Australian driving restrictions: how well do neurologists know them?. Issue 5 (8th May 2017) - Caruana, Patricia; Hughes, Andrew; Lueck, Christian J
Abstract : Objectives: Australian driving regulations are complex. We examined knowledge of these regulations in relation to common neurological conditions. Methods: We developed a questionnaire relating to five common neurological scenarios, specifically transient ischaemic attack, vasovagal syncope, unwitnessed blackout, first seizure and vertigo. We considered these in relation to both private and commercial driving licenses. Correct answers were determined from Austroads: Assessing Fitness to Drive, 2012, rev2013.1. 1 We also asked participants about their experience and to rate their own level of knowledge. Questionnaires were circulated to medical students at the Australian National University and to individuals attending the ANZAN Annual Scientific Meeting in 2016. Results: One-hundred and eighteen questionnaires (26 medical students, 20 neurology registrars and 72 neurology consultants) were suitable for analysis. Overall 6% of participants rated their own knowledge as excellent, 27% good, 41% satisfactory and 21% as poor. The vast majority of the latter group were medical students. 3% of respondents were unaware of the existence of the guidelines. As a group, respondents were correct 59% of the time for private licences and 35% of the time for commercial licenses. For private licenses, the highest correct score was for vasovagal syncope (77% correct) and the lowest for transient ischaemic attack (43% correct). For commercial licences, the highest score was for first seizure (50% correct) and the lowest was vasovagal syncope (9% correct). Consultants gave more accurate responses (54% correct) than medical students (27% correct). Conclusions: These results indicate clearly that education regarding driving restrictions in Australia should be improved and form part of the medical student curriculum. All parties concerned are involved in ensuring that patients adhere to the driving regulations so medical practitioners need to be fully conversant with the guidelines regarding both private and commercial licenses. An update at a future medical conference might be warranted.